Utilization of the Let’s Read application in promoting primary school students’ literacy - Salsabila, Humaira Azka; Apoko, Tri Wintolo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
This study is motivated by the low interest and reading literacy skills of primary school students in Indonesia, which is a significant challenge in the world of education. This study aims to investigate the effectiveness of using the Let's Read application in improving reading literacy and to describe students' perceptions of the application. The participants were 60 fifth-grade students at a public primary school in Eastern Jakarta selected using purposive sampling. The research method used a mixed methods approach, with quantitative data collected through questionnaires and a reading test, and qualitative data through semi-structured interviews. Quantitative data were analyzed using descriptive and inferential statistical tests, while qualitative data were analyzed thematically. The results showed that the Let's Read app positively contributed to improving students' interest, reading comprehension, and learning motivation. However, the difference in scores between the experimental and control groups was not statistically significant. The implication of this study shows that digital technology integration, such as Let's Read, needs to be further developed with more interactive features to improve the effectiveness of literacy learning in primary schools.